Innovation in Talent Management to Enhance Generation Z Retention and Performance - Ramadian, Afzil; Meisyarani, Nara; Dewi, Sri Eka (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
The dynamic development of the labor market demands organizations to innovate in talent management, especially in adapting to the unique characteristics of Generation Z. This study aims to identify and analyze effective retention strategies for Generation Z employees in Indonesia. Using a Systematic Literature Review (SLR) method, this paper synthesizes relevant literature on talent management and employee retention. The findings indicate that innovative talent management—integrating digital technologies, flexible work arrangements, and inclusive organizational culture—is effective in enhancing retention and performance among Generation Z. Practical implications suggest that organizations must design adaptive retention policies aligned with business goals and generational expectations. This study contributes insights into human capital strategies in the digital era.